2016
DOI: 10.7567/jjap.55.05fj02
|View full text |Cite
|
Sign up to set email alerts
|

Study of radiation detection properties of GaN pn diode

Abstract: Recently, GaN, which has remarkable properties as a material for optical devices and high-power electron devices, has also attracted attention as a material for radiation detectors. We previously suggested the use of BGaN as a neutron detector material. However, the radiation detection characteristics of GaN itself are not yet adequately understood. For realizing a BGaN neutron detector, the understanding of the radiation detection characteristics of GaN, which is a base material of the neutron detector, is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…X-ray detectors have widely been used for several applications including nondestructive inspection of industrial goods, medical imaging, security scrutiny, and homeland defense. , High-quality semiconductors are mainly used for fabricating X-ray detectors due to their simple device configuration, high detection sensitivity, and the unique property of directly converting X-rays into desired electrical signals. Among various semiconducting materials, cadmium telluride (CdTe), amorphous selenium (α-Se), and silicon (Si) have been utilized extensively to fabricate commercial direct-mode X-ray detectors and imagers. However, these materials suffer from small Z (atomic number) and/or insufficient mobility-lifetime (μτ) products and high processing costs.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray detectors have widely been used for several applications including nondestructive inspection of industrial goods, medical imaging, security scrutiny, and homeland defense. , High-quality semiconductors are mainly used for fabricating X-ray detectors due to their simple device configuration, high detection sensitivity, and the unique property of directly converting X-rays into desired electrical signals. Among various semiconducting materials, cadmium telluride (CdTe), amorphous selenium (α-Se), and silicon (Si) have been utilized extensively to fabricate commercial direct-mode X-ray detectors and imagers. However, these materials suffer from small Z (atomic number) and/or insufficient mobility-lifetime (μτ) products and high processing costs.…”
Section: Introductionmentioning
confidence: 99%
“…Sugiura, M. et al has recently reported for the first time a p-n diode-based α-particle detector. Figure 4 shows the schematic of GaN p-n diode used for α-particle detection [30]. These p-n diodes exhibited a mobility/life-time product of 4.6 × 10 −5 cm 2 /V which is lower than the values reported for CdTe (~10 −3 cm 2 /V) and TlBr (~10 −3 cm 2 /V).…”
Section: P-n Diodesmentioning
confidence: 93%
“…CCE values above 90% were achieved; however, high voltages were required to reach these CCE magnitudes. , By fabricating a Schottky barrier diode based on a thin GaN layer grown epitaxially on freestanding GaN with a low threading dislocation density, Sandupatla et al were able to achieve good CCE values at lower voltages, more specifically, a CCE above 60% was obtained when applying a reverse bias of 20 V . α Particle detection was also demonstrated using detectors based on p–n and p–i–n junctions. Recently, Hou et al fabricated a detector by growing a GaN p–i–n structure on top of a 350 μm thick GaN substrate. When considering solely the energy deposited in the depletion region of the detector, they measured a CCE of 92% when applying a reverse bias of 50 V. When operating the detector in self-powered mode, the CCE decreased to 31% .…”
Section: Introductionmentioning
confidence: 99%